2020
DOI: 10.21106/ijma.372
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Empowerment and HIV Testing Uptake: A Meta-analysis of Demographic and Health Surveys from 33 Sub-Saharan African Countries

Abstract: Background: There is a growing body of evidence suggesting that women’s empowerment can help achieve better health behaviours and outcomes. However, few have looked at the impact of women’s empowerment on HIV testing in Sub-Saharan Africa (SSA). This study investigated the association between women’s empowerment and HIV testing among women in 33 countries across SSA. Methods: Cross-sectional data from the most recent Demographic and Health Surveys (2005-2018) of 33 countries in SSA were used. Confounder … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…Anaemia in pregnancy by the WHO classification is haemoglobin (Hb) concentration of <11 g/d. 6 Thrombocytopenia, is defined as low platelet count of <100×10 9 /l, with a count <50×10 9 /l considered severe, and <10×10 9 /l considered very severe, while leucopenia was defined as FBC of <3,000x10 9 /l in adult. 25 However, a lower Hb level of <10 g/dl is used by many African clinicians as indication of anaemia in pregnancy in most healthy African women thus falling below the WHO cutoff for anemia.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Anaemia in pregnancy by the WHO classification is haemoglobin (Hb) concentration of <11 g/d. 6 Thrombocytopenia, is defined as low platelet count of <100×10 9 /l, with a count <50×10 9 /l considered severe, and <10×10 9 /l considered very severe, while leucopenia was defined as FBC of <3,000x10 9 /l in adult. 25 However, a lower Hb level of <10 g/dl is used by many African clinicians as indication of anaemia in pregnancy in most healthy African women thus falling below the WHO cutoff for anemia.…”
Section: Methodsmentioning
confidence: 99%
“…The PCV (%) values were converted to Hb (g/dl) by applying the constant factor of 0.3. 27 The Hb concentration, platelet, and CBC levels was divided into two groups:<10 g/dl, and >10 g/dl for Hb, <100 x10 9 /l, and >100 x10 9 /l for the platelet, and <3,000 x10 9 /l, and >3,000 x10 9 /l for the purposes of the study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, in a meta-analysis of 33 sub-Saharan countries, Yaya 2020 18 found no significant relationship between empowerment and HIV testing uptake in more than half of the countries included in their study. This study used a combination of women's role in household decisionmaking and her attitude towards wife-beating as measures of empowerment.…”
mentioning
confidence: 92%
“…14 While more evidence is accumulating within different cultural contexts, there is a lack of consensus on the most accurate measure for empowerment. Various studies have used factors such as literacy/education and wealth, 15,16 or a mixture of attitudes towards women's autonomy (women can refuse sex or ask for condoms), justification of wifebeating 17,18 and women's participating in household major decision-making as indicators of empowerment. 18,19 A study of 29 Sub-Saharan countries 13 found that women who believed they had the right to ask their husbands to use a condom if he had a sexually transmitted infection were more likely to have been tested for HIV.…”
mentioning
confidence: 99%